2011
DOI: 10.1002/mrm.23042
|View full text |Cite|
|
Sign up to set email alerts
|

Fast dynamic contrast‐enhanced lung MR imaging using kt BLAST: A spatiotemporal perspective

Abstract: Dynamic contrast-enhanced MR imaging has long been an attractive alternative to measure pulmonary perfusion as it offers simultaneous acquisition of high-resolution anatomical images and various functional information without exposing to ionizing radiation. As higher temporal resolution in addition to simultaneous acquisition of more slices from different positions favors more precise diagnosis, rapid acquisition of multiple images during bolus contrast administration remains essential to pulmonary perfusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…29 On the other hand, Hsu et al demonstrated that k-t factor of five could be used for contrast-enhanced lung perfusion measurement. 30 Thus, the selection of k-t acceleration factor must be based on the level of tolerance in the motion error as well as the image degradation for a specific purpose. The focus of present study is the application of k-t BLAST based dynamic MRI for the motion management for radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, Hsu et al demonstrated that k-t factor of five could be used for contrast-enhanced lung perfusion measurement. 30 Thus, the selection of k-t acceleration factor must be based on the level of tolerance in the motion error as well as the image degradation for a specific purpose. The focus of present study is the application of k-t BLAST based dynamic MRI for the motion management for radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the intrinsic physical limitation of MRI, the speed of data acquisition is always the problem comparing to CT. Hence, a number of acceleration techniques have been developed over the past four decades and the shortened acquisition time has greatly expanded clinical applications of MRI, especially for dynamic or time-resolved MRI, such as perfusion imaging [103106], contrast-enhanced MR angiography [107111], functional MRI [112, 113], and cardiac function examinations [114117]. Those acceleration techniques could be divided into two categories: parallel imaging and dynamic acceleration.…”
Section: Imaging Acceleration In Magnetic Resonance Imagingmentioning
confidence: 99%